Area contraction effect on shock tube performance, numerical and experimental study - Mohsen M.; Yusoff M.Z.; Al-Falahi A. (Asian Research Publishing Network, 2023)
The paper presents numerical and experimental study on the effect of area contraction in shock tube facility. The shock tube is the main component of short duration test facility at The Universiti Tenaga Nasional (UNITEN), Malaysia. In the shock tube, a small area contraction in form of a removable bush was facilitated adjacent to the diaphragm section. The flow process was simulated using a two-dimensional time-accurate Navier-Stokes solver. The solver uses second order accurate cell-vertex finite volume spatial discretization and fourth orders accurate Runge-Kutta temporal integration. In this study, the solver was programmed based on the dimensions and configuration of UNITEN's shock tube facility. The numerical results were validated with experimental data from the ground based test facility. Numerical pressure histories were found to be in accordance with the experimental data. For further investigations, simulations were conducted for different operating conditions. The results showed that shock tube performance in term of producing shock wave and steady gas flow is highly influenced by area contraction in the diaphragm section. The shock wave strength and speed decreased by 18% and 8% respectively. 2006-2015 Asian Research Publishing Network (ARPN).